2011
DOI: 10.1021/nn1025719
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hexahistidine in Directed Nanoassemblies of Tobacco Mosaic Virus Coat Protein

Abstract: A common challenge in nanotechnology is the fabrication of materials with well-defined nanoscale structure and properties. Here we report that a genetically engineered tobacco mosaic virus (TMV) coat protein (CP), to which a hexahistidine (His) tag was incorporated, can self-assemble into disks, hexagonally packed arrays of disks, stacked disks, helical rods, fibers, and elongated rafts. The insertion of a His tag to the C-terminus of TMV-CP was shown to significantly affect the self-assembly in comparison to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 46 publications
2
60
0
Order By: Relevance
“…10À17 However, these genetic and chemical techniques require time-consuming optimization for each desired material interaction and may result in modifications that interfere with the intrinsic self-assembly properties of the scaffold. 18 Received: May 24, 2011 ABSTRACT: Natural systems often utilize a single protein to perform multiple functions. Control over functional specificity is achieved through interactions with other proteins at well-defined epitope binding sites to form a variety of functional coassemblies.…”
Section: ' Introductionmentioning
confidence: 99%
“…10À17 However, these genetic and chemical techniques require time-consuming optimization for each desired material interaction and may result in modifications that interfere with the intrinsic self-assembly properties of the scaffold. 18 Received: May 24, 2011 ABSTRACT: Natural systems often utilize a single protein to perform multiple functions. Control over functional specificity is achieved through interactions with other proteins at well-defined epitope binding sites to form a variety of functional coassemblies.…”
Section: ' Introductionmentioning
confidence: 99%
“…To our knowledge, there is no work thus far describing the expression of a His-tagged potyviral CP that assembles into VLPs. TMV studies have demonstrated a pivotal role of His-tag on controlling assembly of CP monomers to different virus-like structures, like rings, discs, rods, and filamentous structures [18, 19]. However, despite the potential of affinity tags, like hexahistidine, to facilitate process development of proteins, these may have undesired consequences on protein stability in solution and immunogenicity [20].…”
Section: Resultsmentioning
confidence: 99%
“…The ability to control and modify the formation of assembly intermediates represents a powerful means to produce novel ePVN structures that would not form under native conditions. Previous studies have expressed TMV CP and shown that under physiological conditions (neutral pH) these purified CPs form only lower order assemblies that include small aggregates and disks (Bruckman et al, 2011;Dedeo et al, 2010Dedeo et al, , 2011Miller et al, 2007). Recently, a bacterial optimized TMV CP ORF was modified by substituting charge neutralizing amino acids Q and N at position E50 and D77, respectively .…”
Section: Strategies For Epvn Production and Controlled Assemblymentioning
confidence: 99%
“…Bruckman et al genetically inserted a hexa-histidine tag on the Cterminus of the TMV CP (Bruckman et al, 2011). Bacterial expressed and purified CPs showed altered assembly profiles, forming hexagonal disk arrays and rafts of elongated rods whose assembly could be controlled by the concentration of nickelnitrilotriacetic acid.…”
Section: Strategies For Epvn Production and Controlled Assemblymentioning
confidence: 99%